Whither the World Trade Organisation? Perspective of key WTO ambassadors on current challenges in global trade talks - Sherman Katz (European Centre for International Political Economy (ECIPE), 2015)
What are the challenges facing negotiators at the World Trade Organisation (WTO)? By the end of this year, Trade Ministers will meet in Nairobi for a WTO Ministerial Meeting and current talks in Geneva centre upon the idea of drafting a work programme that would set the direction for concluding the Doha Round. While the successful end of the Bali Agreement has ushered in some new optimism about the Doha Round, key challenges remain. This Policy Brief offers a survey of views from key stakeholders in Geneva - with a focus on the structural challenges and ways to address them. The role of emerging markets in the Doha Round is important. Many countries are focusing on China and its rapidly growing importance for the world trading system. While it joined the WTO shortly after the launch of the Round, and thus claims Recently Acceded Member status, several countries are keen to get China to "pay" in the Doha Round - to offer improved market access. Several key Geneva stakeholders speak about the necessity of a deal between China and the United States for the Round to get to a conclusion. There is increasing talks about moving away from the formulas used in the negotiations over market access in agriculture and goods. A request-and-offer approach has been suggested - and one of the implications could be that, while the ambitions for the negotiations are lowered, attention is given to the tariffs that distort trade the most.
Keywords: 330; WTO-Verhandlungen